Elastic Differential Cross Sections for Electron Scattering with Dichloromethane - Lange, E. (2017)
Synopsis In the present study joint experimental and theoretical elastic differential cross sections for electron scattering from dichloromethane in the incident electron energy region 7 to 50eV are discussed.